First Term Outcomes of a Young Surgeon in Inguinal Hernia Repair: Lichtenstein, TAPP, and TEP - Ergün, Sefa; Akıncı, Ozan (Cerrahpaşa Medical Journal, 2021)
Background: In this study, we aimed to compare the early outcomes of inguinal hernia repairs performed by a young general surgeon with Lichtenstein, trans abdominal pre-peritoneal (TAPP), and total extraperitoneal (TEP) techniques. Methods: Ninety patients who were operated on by a single surgeon with the diagnosis of inguinal hernia in Avcılar State Hospital between March 2018 and March 2020 were evaluated retrospectively. The patients were divided into 3 groups as Lichtenstein, TAPP, and TEP. Duration of operation, length of hospital stay, perioperative complications, chronic pain, and recurrence parameters were compared. Results: Eighty-one of the patients were male and 9 were female. Lichtenstein, TAPP, and TEP groups included 30, 31, and 29 patients, respectively. The distribution of hernia localization, hernia type, and the number of recurrence cases of the groups was similar. No significant differences were found between the groups in terms of operation time and length of hospital stay (P > .05). There were no significant differences between the intraoperative and postoperative complication rates of the groups (P = .799 and P = .594, respectively). The rate of postoperative chronic pain was 5.5% in all cases and 6.45%, 3.44%, and 6.66% in the TAPP, TEP, and Lichtenstein groups, respectively (P = .999). Recurrence was observed in 5 cases in Lichtenstein, 2 in TEP, and 1 in TAPP (P = .164). Conclusion: Operation time, length of hospital stay, perioperative complications, and recurrence rates are similar in open and laparoscopic inguinal hernia repairs. Laparoscopic techniques are also safe and useful for young surgeons with surgical competence. Cite this article as: Ergün S, Akıncı O. First term outcomes of a young surgeon in inguinal hernia repair: Lichtenstein, TAPP, and TEP. Cerrahpaşa Med J. 2021;45(3):141-146.